Jama’ah Tabligh’s Perspectives on Misogynistic Hadiths - Sabri, Muhammad; Safri, Edi; Sarwan, Sarwan (Universitas Islam Negeri Imam Bonjol Padang, 2023)
This study aims to explore the understanding of the Jama'ah Tabligh of Masjid Muhammadan, whose understanding of misogynistic hadiths tends to be contextual. It is interesting for the author to explore what factors influence the dynamism of the Jama'ah Tabligh's understanding of hadiths, as the paradigm about the Jama'ah Tabligh is gender-biased and understanding hadiths in a literal-textual manner. The problem to be examined is to explore the Jama'ah Tabligh's understanding of the hadith about a wife's reluctance to have intimate relations with her husband, a wife's entry into paradise with the husband's consent, and what factors underlie the dynamism of their thinking. This research uses a descriptive qualitative method with a phenomenological and gender approach. The data collection techniques used are semi-structured interviews with Jama'ah Tabligh of Masjid Muhammadan who have become 'amir in khuruj (selected objectively) and documentation, namely the books Riyadhus Shalihin and Fadhail 'Amal. The findings of this study are that in the matter of intimate relationships and wives' obedience to their husbands, they tend to be fair and balanced, treating their wives humanely and in accordance with Islamic teachings, while the factors underlying their thinking are the ideologies they embrace, which consist of Muhammadiyah and NU. Thus, it can be concluded that the Jama'ah Tabligh of Masjid Muhammadan tends to be contextual in understanding misogynistic hadiths, as the issue of the husband-wife relationship for them must consider the condition of a wife (intimate relationships and obedience of the wife). Furthermore, the dynamic reception of the Jama'ah Tablig is believed that they are no longer fanatical about the Jama'ah Tabligh ideology itself, but rather bring their own ideologies into the Jama'ah Tabligh group.